第59次日本南極地域観測隊気象部門報告2018 - 杉山, 暢昌; スギヤマ, ノブマサ; Sugiyama, Nobumasa; 出原, 幸志郎; デハラ, コウシロウ; Dehara, Kohshiro; 島村, 翔; シマムラ, ショウ; Shimamura, Sho; 田中, 省吾; タナカ, ショウゴ; Tanaka, Shogo; et al. (国立極地研究所, 2022)
この報告は第59 次日本南極地域観測隊気象部門が2018 年2 月1 日～2019 年1 月31 日まで昭和基地にて行った気象観測結果をまとめたものである．観測方法や測器，統計方法等は高層気象観測の測器を除き，第58 次隊と同様である．越冬期間中の特記事項としては次のものがあげられる． 1）2018 年3 月20 日から明星電気製RS-06G 型GPS ゾンデを同社製RS-11G 型 GPS ゾンデに更新． 2）高精度で連続性のある高層気象観測網であるGRUAN（GCOS Reference Upper Air Network）のリードセンターへ観測データ等の報告を開始． 3）YOPP-SH（Year Of Polar Prediction in the Southern Hemisphere）への協力としての，高層気象観測の強化実施． 4）7 回の顕著な地上オゾン消失現象（Surface Ozone Depletion: SOD）の出現を確認． This report describes the results of meteorological observations at Syowa Station from February 1st, 2018 to January 31st, 2019, carried out by the Meteorological Observation Team of the 59th Japanese Antarctic Research Expedition (JARE-59). The observation methods and instruments, statistical methods used by JARE-59 were almost the same as those used by the JARE-58 observation team. Topics during the period of JARE-59 are as follows. 1) Updated the Meisei Electric RS-06G type GPS radiosonde to the Meisei Electric RS-11G type GPS radiosonde from March 20, 2018. 2) Started to report observation data to the lead center of GRUAN (GCOS Reference Upper Air Network), a high-precision, continuous upper air observation network. 3) Strengthening of upper air observation in cooperation with YOPP-SH (Year Of Polar Prediction in the Southern Hemisphere). 4) Confirmed seven times SODs (Surface Ozone Depletions) were appeared. departmental bulletin paper